The role of physical acgtivity in life satisfaction and psychological resilience among college students: Mediating effects of self-efficacy and perceived stress - Rujiang Zhang (PLoS ONE, 2025)
Background With the increasing global attention on mental health issues, especially the psychological stress and life satisfaction problems faced by college students, it has become particularly important to explore how physical activity is associated with college students’ psychological resilience and quality of life through psychological mechanisms. This study aims to examine the association between physical activity on college students’ life satisfaction and psychological resilience, and to investigate the mediating roles of self-efficacy and perceived stress. Methods This study collected data from college students in several universities in China through online questionnaires, using the Body Self-Concept Questionnaire, Life Satisfaction Scale, the Chinese Revised Version of the Connor–Davidson Resilience Scale, General Self-Efficacy Scale, and Perceived Stress Scale to measure each variable. A total of 560 undergraduate students from three universities participated in the survey, reporting on their physical activity, life satisfaction, psychological resilience, self-efficacy, and perceived stress. Results The findings show that physical activity was significantly associated with higher life satisfaction (r = 0.439, p < 0.001) and psychological resilience (r = 0.521, p < 0.001). Both self-efficacy (95% CI = [0.138, 0.255] and [0.245, 0.399]) and perceived stress (95% CI = [0.013, 0.070] and [0.040, 0.134]) played significant mediating roles in these processes. Specifically, physical activity was linked to better mental health and quality of life through its association with higher self-efficacy and lower perceived stress. Discussion and implications This study validates the association between physical activity and improved college students’ life satisfaction and psychological resilience and reveals the mediating mechanisms of self-efficacy and perceived stress. These findings provide a scientific basis for designing exercise and psychological intervention programs for college students, with important practical implications.